2021
DOI: 10.1007/s00277-021-04650-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of autologous stem cell transplantation (ASCT) in aggressive B-cell lymphomas: real-world data from a retrospective single-center analysis

Abstract: Patients with high-risk or relapsed aggressive B-cell lymphomas are characterized by poor prognosis. High-dose chemotherapy followed by autologous stem cell transplantation (ASCT) can induce durable remissions in these patients and is potentially curative. Two hundred forty-seven patients with aggressive B-cell lymphomas treated with high-dose chemotherapy and ASCT, either as consolidation after first-line therapy or after salvage therapy for relapsed disease, between 2002 and 2019 at the University Hospital M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
(87 reference statements)
1
8
1
Order By: Relevance
“…The studied population is representative of the current indications for ASCT in lymphoma [1,14] and consistent with recent registry reports [15,16].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The studied population is representative of the current indications for ASCT in lymphoma [1,14] and consistent with recent registry reports [15,16].…”
Section: Discussionsupporting
confidence: 82%
“…We chose to focus on transfusion support and relevant clinical information such as the severe toxicities or infectious complications that impact the duration of pancytopenia were not analysed. Evaluating the efficacy of transplantation was outside this study's scope, but the low transplantation-related mortality (0.4%), the duration of admission and the engraftment times were in line with those expected [4,[16][17][18].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Several previous studies have demonstrated a linkage between higher collected graft CD34 + cell count and improved survival after ASCT in NHL patients [5][6][7]21]. None of these studies have included more detailed graft composition analyses.…”
Section: Discussionmentioning
confidence: 99%